PENGARUH QUICK RATIO, TOTAL ASSETS TURNOVER, RETURN ON ASSETS, DEBT TO TOTAL ASSETS TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Intan Veronica; Suyatmin Waskito Adi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of Quick Ratio (QR), Total Assets Turnover (TATO), Return On Assets (ROA), Debt To Total Assets (DAR) on stock prices. The population in this study is industrial companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The data used is taken from the financial statements of industrial companies for 2018-2020. The sample in this study was determined by purposive sampling method, so that the sample that met the criteria for taking the sample in this study were 35 companies. The data analysis model used is multiple linear regression model. Based on the results of this study indicate that the first hypothesis Quick Ratio (QR) has no effect on stock prices, the second hypothesis Total Assets Turnover (TATO) has no effect on stock prices, the third hypothesis Return On Assets (ROA) has an effect on stock prices, and the fourth hypothesis Debt To Total Assets (DAR) has no effect on stock prices in industrial companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020.